2008
DOI: 10.1016/j.drugalcdep.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Drug use in the social networks of heroin and cocaine users before and after drug cessation

Abstract: The present study examined Social Control processes in drug cessation among adults. Social Control theory posits that the association between drug use and the drug use of a person's social network results from an individual seeking out similar peers. The data included 629 individuals who reported past-year heroin or cocaine use at baseline and had follow-up data in a community study in Baltimore, MD. Negative binomial regression modeling indicated that the reduction in social network drug use was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 17 publications
0
60
1
2
Order By: Relevance
“…Place of residence influences exposure to drugs and violence and potential vulnerability to long-term drug use. 28 Studies have shown that neighborhood drug access 29 and social network drug influences 30 can present substantial challenges to drug cessation. In this sample, involvement in the drug economy was not associated with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Place of residence influences exposure to drugs and violence and potential vulnerability to long-term drug use. 28 Studies have shown that neighborhood drug access 29 and social network drug influences 30 can present substantial challenges to drug cessation. In this sample, involvement in the drug economy was not associated with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Many persons with severe and prolonged AOD problems migrate toward heavy AOD using cultures as these problems intensify (Buchanon & Latkin, 2008). Such cultures have been extensively described in the early ethnographic literature on addiction (Agar, 1973;Bahr, 1973;Spradley, 1970;Waldorf, 1973).…”
Section: Cultures Of Addiction and Recoverymentioning
confidence: 94%
“…It is estimated that that around 10 million IDU are HCV positive and around 1 million are HBV positive (Nelson, et al, 2011). Prevalence estimates of HCV infection exceed 50% in most IDU populations, and can range as high as 95%; prevalence of chronic HBV is estimated at 8.4% (Buchanan & Latkin, 2008). East Asia, and Southeast Asia have among the largest populations of IDU infected with viral hepatitis (Nelson, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%